تقييم سمات الثقافة التنظيمية السائدة في المشافي الحكومية (المصنفة كهيئة مستقلة) في مدينة طرطوس (Latakia University Journal -Medical Sciences Series, 2019)
تقييم سمات الثقافة التنظيمية السائدة في المشافي الحكومية (المصنفة كهيئة مستقلة) في مدينة طرطوس رلى عليو عدنان بدور رهام أحمد يشكل مفهوم الثقافة التنظيمية عاملاً ضرورياً في تحسين الرعاية الصحية، لأنه يمكن أن يدعم أو يعيق عمل الكادر التمريضي في المشفى. لذا هدفت هذه الدراسة إلى تقييم سمات الثقافة التنظيمية السائدة في مشفى الباسل ومشفى الشهيد مجد عبدالله )المصنفة كهيئة مستقلة( في مدينة طرطوس، وذلك من وجهة نظر عناصر الكادر التمريضي الذين تم اختيارهم بطريقة العينة المتاحة من مختلف الأقسام (n=411) حيث تم توزيع استبيانDenison  لتقييم الثقافة التنظيمية (DOCS) العينة المشاركة على جميع أفراد العينة المشاركة. أظهرت النتائج أن سمة الثقافة التنظيمية السائدة هي التكيف بنسبة (65%) يليها سمة المشاركة (63%) ثم سمة التماسك (62.4%) بينما كانت سمة الرسالة أو المهمة أقل سمة موجودة (49.6%). وأوصت الدراسة بضرورة تعزيز سمات الثقافة التنظيمية الهامة في المستشفيات والتي تساهم في تحسين بيئة الرعاية الصحية مثل سمتي التماسك والرسالة. بالإضافة إلى ذلك فإن إجراء دراسات مماثلة على نطاق أوسع تشمل المزيد من المستشفيات وتستخدم أدوات مختلفة قد يُفيد في فهم الثقافة التنظيمية بشكل أفضل. The concept of organizational culture has been a necessary factor in improving health care because it can support or hinder the work of nursing stuff in the hospital. Therefore, this descriptive cross sectional survey study was designed to evaluate the organizational culture traits in Al-Basel Hospital and Majd Abdulla Hospital (classified as independent Trusts) in the city of Tartous, from the point of view of nursing stuff selected by convenient sampling from different departments (n=411). Denison Organization Culture Survey (DOCS) questionnaire was distributed to all participants. The results showed that the prevailing organizational cultural trait was adaptability (65%), followed by involvement (63%), consistency (62.4%), and the lowest trait was mission (49.6%). The study recommended the need to enhance important organizational culture traits in hospitals which contribute to improving the health care environment such as consistency and mission traits. In addition,  conducting similar studies on a larger scale involving more hospitals and using different instrumentations would also improve the understanding of organizational culture.